Retrievability of Fractured Abutment Screws and Damage to Implant–Abutment Connections: An In Vitro Comparative Analysis of Conventional vs. Drilling Techniques - Paloma Martínez-Alcaraz; Javier Flores-Fraile; Rubén Agustín-Panadero; Gisela Senent-Vicente; Cristina Gómez-Polo; Silvia de la Cruz-Jiménez; Álvaro Zubizarreta-Macho; Ana Belén Lobo Galindo (Applied Sciences)
This study aimed to evaluate the retrievability and potential damage to implant–abutment connections caused by fractured abutment screw removal using conventional and drilling techniques. A total of forty abutment screws were randomly inserted into forty dental implants, and then they were fractured and extracted using different removal methods: Group A employed a conventional approach utilizing an exploration probe and an ultrasonic device without irrigation (n = 10) (conventional); Group B used the Phibo drilling removal system without irrigation (n = 10) (Phibo); Group C utilized the Rhein83® drilling removal system without irrigation (n = 10) (Rhein83); and Group D implemented the Sanhigia® drilling removal system without irrigation (n = 10) (Sanhigia). Pre- and postoperative micro-computed tomography (micro-CT) scans were performed on the dental implants, and Standard Tessellation Language (STL) digital files were generated for morphometric analysis to measure the wear volume. ANOVA was used to assess the volumetric differences (mm3) and percentage ratios of the internal thread volumes of the implant–abutment connections before and after the procedures. Results: This study found no statistically significant differences in the volumetric and percentage ratios of internal threads among the implant groups (Phibo, Rhein83, Sanhigia, and conventional). However, the success rate for retrieving fractured abutment screws was higher (90%) with the drilling systems compared to the conventional technique (50%). These results suggest that drilling systems are more effective for the retrieval of damaged screws. Although drilling techniques without irrigation demonstrated higher removal efficiency compared to the conventional method, both approaches resulted in similar wear volumes at the implant–abutment connections when used to extract fractured screws.